Efectos sociales y jurídicos del uso referente de la prisión preventiva en la audiencia de calificación de flagrancia en el cantón Pasaje, provincia de El Oro en el periodo 2012-2013. - Armijos Valle, Jonathan Giovanni (2013)
In the present investigation, the hypothesis has been defined that the inadequate use of pretrial detention in flagrancy qualification hearings has distorted the purpose of this precautionary measure, turning it into a first-hand tool in criminal proceedings, as well as being used as Compensatory penalty and in an anticipated penalty.